Inovasi Kurikulum Terintegrasi Tafaqquh Fiddin Di Madrasah Aliyah Persis Bentar Kabupaten Garut Jawa Barat - Riyan Nuryadin; Siti Aini Latifah Awaliyah; Peri Gunawan; Rahmat; Qiqi Yuliati Zaqiah Qiqi Yuliati Zaqiah (At Turots: Jurnal Pendidikan Islam, 2025)
This study examines the innovation of the integrative Tafaqquh Fiddin curriculum at Madrasah Aliyah Persatuan Islam (Persis) Bentar, Garut, as a response to the challenges of globalization, the dichotomy of knowledge, and the need for contextual Islamic education. The curriculum integrates the national curriculum of the Ministry of Religious Affairs with the distinctive Persis curriculum, which is rooted in manhaj tarjih, aqidah salimah, and the spirit of scholarly jihad. The integrative approach includes strengthening religious subjects through the addition of courses such as Ushul Fiqh, Qawaid Fiqhiyyah, and Maqashid al-Shari’ah, alongside the study of tarjih texts and contemporary fiqh. This research employs a qualitative-descriptive approach with a case study design, utilizing observation, interviews, and documentation at Madrasah Aliyah (MA) Persis Bentar Garut. The findings indicate that this curriculum innovation not only eliminates the dichotomy between religious and general sciences but also fosters the development of students’ religious character, critical thinking skills, and social sensitivity. The curriculum integration is implemented through intracurricular, co-curricular, and extracurricular activities, thereby creating a holistic, authentic, and contextual learning ecosystem. The implications of this study contribute to the development of a modern model of Islamic education that is grounded in traditional values while responsive to contemporary needs.